The Effect of Product Quality and Price Perception on Purchase Decisions Through Brand Trust on Zoya Fashion Products in Pekanbaru City - Futri Janila Andani; Jushermi Jushermi; Agnes Alvionita (Westscience Press, 2026)
This study aims to analyze the impact of product quality and price perception on buying decisions through brand trust regarding Zoya fashion products in Pekanbaru City. With the increasing interest of the public in Muslim fashion, Zoya, as one of the leading brands, faces challenges in maintaining its market share. The research method used is a survey with a questionnaire involving 100 respondents who are Zoya consumers. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS).The results show that (1) product quality has a significant positive effect on brand trust; (2) price perception also has a significant positive effect on brand trust; (3) product quality significantly positively influences purchase decisions; (4) price perception has a significant negative effect on purchase decisions; (5) brand trust significantly positively influences purchase decisions; (6) brand trust mediates the effect of product quality on purchase decisions; and (7) brand trust mediates the effect of price perception on purchase decisions